2014
DOI: 10.1016/j.electacta.2014.03.099
|View full text |Cite
|
Sign up to set email alerts
|

Redox, surface and electrocatalytic properties of layer-by-layer films based upon Fe(III)-substituted crown polyoxometalate [P8W48O184Fe16(OH)28(H2O)4]20-

Abstract: have been utilized to monitor the construction of the LBL film after the deposition of each monolayer. The electrochemical behaviour of both a cationic and anionic 2 redox probes at the LBL films has been undertaken to give indications as to the film's porosity. The elemental composition and the surface morphology of the LBL films was conifmrde through the employment of AFM, XPS and SEM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 69 publications
0
11
0
Order By: Relevance
“…Nitrate is hardly reduced to nitrite, while the nitrite reduction to nitric oxide (NO) and to further reduced products down to ammonia is facilitated with the addition of transition-metal ions to the W–O cage. However, the nitrate electrocatalysis attributes are not all transition-metal multisubstituted HPA …”
Section: Resultsmentioning
confidence: 99%
“…Nitrate is hardly reduced to nitrite, while the nitrite reduction to nitric oxide (NO) and to further reduced products down to ammonia is facilitated with the addition of transition-metal ions to the W–O cage. However, the nitrate electrocatalysis attributes are not all transition-metal multisubstituted HPA …”
Section: Resultsmentioning
confidence: 99%
“…17 Feng, Mullen and Bubeck et al reported ESA lms consisting of H 3 PW 12 O 40 and GO with poly(allylamine hydrochloride) as the base lm and PDDA as their interlayer linker, where the GO layer could be photoreduced by UV photocatalytic POM, and eld effect transistors based on these composite lms exhibited typical ambipolar features. 23,24 However, layer-by-layer multilayer lms based on Ru(II) complexes and GO have not been extensively explored (see Fig. 23,24 However, layer-by-layer multilayer lms based on Ru(II) complexes and GO have not been extensively explored (see Fig.…”
Section: Introductionmentioning
confidence: 99%
“…18 Ru(II) polypyridyl complexes have attracted tremendous interest as key components in nanosized thin lms with widespread applications, due to their strong visible light absorption, as well as unique photochemical, photophysical and redox properties. 23,24 However, layer-by-layer multilayer lms based on Ru(II) complexes and GO have not been extensively explored (see Fig. 1 for the molecular structures of Ru(II) complexes used for their ESA lms with GO).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…26,27 POM has been shown to have a good electrocatalytic properties toward the reduction of hydrogen peroxide and undergo multiple electron transfer. 28,29 The voltammetry measurements on POM−PPyMP-modified electrodes showed the appearance of a cathodic wave accompanied by a decrease in anodic counterpart currents (Figure 2B) upon the addition of hydrogen peroxide. In contrast, pure PPyMPs showed insignificant electrocatalytic activities (Figure 2B, insert).…”
Section: ■ Results and Discussionmentioning
confidence: 99%